Harvesting, Isolation, and Functional Assessment of Primary Vagal Ganglia Cells. Issue 1 (16th February 2018) - Dubuis, Eric; Grace, Megan; Wortley, Michael A.; Birrell, Mark A.; Belvisi, Maria G.
Abstract: Airway sensory nerves play an important defensive role in the lungs, being central in mediating protective responses like cough and bronchoconstriction. In some cases, these responses become excessive, hypersensitive, and deleterious. Understanding the normal function of airway nerves and phenotype changes associated with disease will help in developing new therapeutics for treating chronic obstructive pulmonary disease and chronic cough. Guinea pigs, and to a lesser extent ferrets, are commonly employed for studying the cough reflex because they have a cough response similar to humans. While rats and mice do not exhibit a cough response, they do possess sensory nerves that respond to the same range of tussive stimuli as guinea pigs and humans. Described in this unit are protocols for harvesting guinea pig, mouse, and rat sensory nerve cell bodies to assess molecular and functional changes associated with pulmonary disease, and to identify new targets for therapeutic intervention. Curr. Protoc. Pharmacol . 62:12.15.1‐12.15.27. © 2013 by John Wiley & Sons, Inc.